Genome-wide association study of tocopherols (vitamin E) in Indian mustard (Brassica juncea): Genome-wide association study of tocopherols (vitamin E) in Indian mustard (Brassica juncea) - HARJEEVAN KAUR; SANJULA SHARMA; JAVED AKHATAR; JOMIKA DEVI; CHHAYA ATRI; S S BANGA (Journal of Oilseeds Research, 2023)
A diverse set of 289 mustard accessions was used to establish variation for α-, γ- and total tocopherols in mustard germplasm. A large variation in our diversity panel for tocopherol isomers and total tocopherols. γtocopherols were observed to be more abundant than α-tocopherols in the mustard seeds. This tocopherol variation was used to identify the genetic loci related to tocopherols using GWAS. Various strong candidate genes such as VTE2-2, SAHH2, PP5.2, PES1, ANT1 etc. involved directly or indirectly in the tocopherol biosynthesis pathway were identified through this method.